Assessment and feedback in higher education : a guide for teachers - McConlogue, Teresa (UCL Press, 2020)
Assessment and Feedback in Higher Education is a concise overview of assessment theory and practice in higher education. Teachers are encouraged to examine their practice critically, and there are ideas for small-scale educational investigations, involving teachers, their colleagues and students.